Whiteness Constructed in a Multicultural World - Aakerhielm, Renate (International Journal of Economic Practices and Theories, 2014)
Many garment producers act on a global market, where people from different cultures often move from countries to others, as well as surf in a world-wide virtual space. In this context, garment producers design their marketing communication efforts considering identity and personality related to the target group aimed at. Often they choose models for their ads, which mirror ideals that the generally defined target group is attracted by. Garment producers often succeed in picking models or icons, which fit well into the social class standards, which the target group identifies with. Nevertheless, they often do this without reflecting on the icons’ identity-and personality-value across cultural differences as colour of the skin, gender and sexuality. Consequently, global standardised advertisements contain stereotypes or standardised personalities. It is common these stereotypes are dominated by whiteness. A possible understanding of “whiteness” is as follows: “lifestyles of white human beings, non-coloured persons”. One question is how whiteness is being constructed in the contemporary visual culture of marketing fashion design. By examining four advertisements of brands providing life-style values, this paper aims at better understanding the lifestyle concept of whiteness. This understanding is of actual interest to a garment producer when designing advertisements. A lack of understanding diminishes the producer’s chance of digging all the market-potential. Three brands closely connected to adored white ideal lifestyles are examined. Furthermore, the brands are in a middle-prize segment and act world-wide on a global market. The study shows, whiteness is represented by wealth, financial independence, power, old traditions, cultural interest and education, sport, leisure, power for life and happiness in life. Further, it appears from the study, whiteness is connected to the American dream. In summary, whiteness is plenty of stereotyping. A conclusion is, the concept of whiteness is far to narrow to fit a global garment producer.